Evaluating the Democratic Quality of Local Democratic Practices – Sampling Seven Frameworks - Löfgren, Karl; Agger, Annika (Scandinavian Journal of Public Administration, 2021)
There has been an upsurge in more participatory, interactive and citizen-oriented governance practices all around the world since the 1990s. What they all have in common is an emphasis on mobilising citizens and stakeholders affected, strengthening local communities, ensuring efficient planning solutions, and securing enhanced legitimacy for existing governing institutions. Conversely, we have witnessed a growing interest in designing frameworks for evaluating the democratic quality of these innovations, asking questions such as the extent to which they actually are enhancing the quality of democracy? This article juxtaposes seven recent evaluative frameworks developed by academics, which address the question of the democratic quality of these new democratic innovations. The article concludes that there are many overlaps between the different frameworks in terms of criteria with a mix of traditional and more participatory democratic norms at play. Furthermore, it also concludes these evaluative practices in many ways reflect the managerial search for accountability mechanisms in the public sector.